2019
DOI: 10.1002/jcp.28799
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Upregulated microRNA‐15b alleviates ovarian cancer through inhitbition of the PI3K/Akt pathway by targeting LPAR3

Abstract: Ovarian cancer characterizes as the fourth leading consequence of death associated with cancer for women. Accumulating evidence underscores the vital roles of microRNAs (miRNAs) in preventing ovarian cancer development. Besides, induction of the phosphatidylinositol-3 kinase/serine/threonine kinase (PI3K/Akt) pathway associated with the ovarian cancer cell migration and invasion. The study aims to examine the effects of miR-15b on the proliferation, apoptosis, and senescence of human ovarian cancer cells by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Furthermore, another subtype of EOC, ovarian clear cell carcinomas (OCCCs), shows more frequently mutations of PIK3CA (33%) and PTEN (5%) in overall 97 OCCC cases, especially mutations of PIK3CA (46%) in the 28 cases of affinity purified OCCCs and OCCC cell lines [192], than the mutation of PIK3CA and PTEN (both < 5%) in HGOSC [193]. Huge amounts of studies have shown YAP, PKG II, SIK2, SERPIND1, miR-15b, -21, -150, -222-3p, -337-3p, -497, -503 and -936, as well as LncRNA MALAT1 and JPX modulate proliferation, apoptosis, invasion, migration, angiogenesis, progression, glucose metabolism or drug resistance of OC cells by PI3K/AKT pathway [194][195][196][197][198][199][200][201][202][203][204][205][206][207]. Some clinical trials of PI3K/AKT inhibitors or in combination with chemotherapy drugs listed in Tables 2 and 3 may help relieve the patients of OC. Along with recent compelling evidence that OSC actually arises from the epithelial lining of fallopian tube, the true incidence of primary fallopian tube carcinoma (PFTC) has been substantially underestimated, which was previously considered as a rare neoplasm accounting for 0.14-1.8% of genital malignancies [208,209].…”
Section: Nct02240212mentioning
confidence: 99%
“…Furthermore, another subtype of EOC, ovarian clear cell carcinomas (OCCCs), shows more frequently mutations of PIK3CA (33%) and PTEN (5%) in overall 97 OCCC cases, especially mutations of PIK3CA (46%) in the 28 cases of affinity purified OCCCs and OCCC cell lines [192], than the mutation of PIK3CA and PTEN (both < 5%) in HGOSC [193]. Huge amounts of studies have shown YAP, PKG II, SIK2, SERPIND1, miR-15b, -21, -150, -222-3p, -337-3p, -497, -503 and -936, as well as LncRNA MALAT1 and JPX modulate proliferation, apoptosis, invasion, migration, angiogenesis, progression, glucose metabolism or drug resistance of OC cells by PI3K/AKT pathway [194][195][196][197][198][199][200][201][202][203][204][205][206][207]. Some clinical trials of PI3K/AKT inhibitors or in combination with chemotherapy drugs listed in Tables 2 and 3 may help relieve the patients of OC. Along with recent compelling evidence that OSC actually arises from the epithelial lining of fallopian tube, the true incidence of primary fallopian tube carcinoma (PFTC) has been substantially underestimated, which was previously considered as a rare neoplasm accounting for 0.14-1.8% of genital malignancies [208,209].…”
Section: Nct02240212mentioning
confidence: 99%
“…Former studies have revealed the regulatory function of LPAR3 and EGFR in cancers. For example, LPAR3 acts as a target gene of miR-15b that alleviates tumor growth in ovarian cancer [16]. EGFR was upregulated by FOXK2 in colorectal cancer to enhance the metastasis of colorectal cancer cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT/mTOR pathway is commonly accepted as a vital pathway in controlling cancer progression, and lncRNA as ceRNA has been validated to mediate tumorigenesis and development through PI3K/AKT/ mTOR pathway [24,25]. LPAR3 has been manifested to be tightly related to PI3K/AKT pathway in ovarian cancer [16]. Moreover, the close association between EGFR and PI3K/AKT/mTOR pathway has been highlighted in some cancer-related studies [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPAR1 plays a paramount role in the invasion, proliferation, migration, and development of ovarian serous cystadenocarcinoma (OSC) intratumoral heterogeneity (ITH) by regulating the activity of PI3K/AKT signaling pathway [54]. When miR-15b was up-regulated, the proliferation of ovarian cancer cells and their apoptosis and senescence were prohibited by the LPAR3-PI3K/Akt pathway [59]. PKCα: protein kinase Cα; PKCγ: protein kinase Cγ; LPAR: lysophosphatidic acid receptors; CXCL12: CXC motif ligand 12; HIF-1α: hypoxia-inducible factor-1α; SPC: smooth muscle progenitor cells; CTGF: connective tissue growth factor; BMSC: bone marrow-derived mesenchymal stem cells; ECM: extracellular matrix; SREBP1: sterol-regulatory element binding proteins 1; TGF-β1: transforming growth factor β1; NADPH: nicotinamide adenine dinucleotide phosphate; RA: rheumatoid arthritis; ERK: extracellular regulated protein kinases; cPKC: classical protein kinase C; MAGI-3: inverted orientation-3; NHERF-2: Na + /H + exchange regulatory factor-2; MAPK: mitogen-activated protein kinase; cAMP: cyclic adenosine monophosphate; PKD: protein kinase D; BBB: blood-brain barrier.…”
Section: Lpar and Ovarian Cancermentioning
confidence: 99%